Mastering the fundamentals of Cytotoxic drug reconstitution and parenteral nutrition / Nik Aisyah Najwa Nik Mustaffa Shapri, Associate Prof. Dr. Mahmathi Karuppannan - Nik Mustaffa Shapri, Nik Aisyah Najwa; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 10th October 2023, the Department of Clinical Pharmacy (DoCP), under the course PHC671 Applied Therapeutics in Infectious Diseases and Neoplastic Disorders organized a workshop on the fundamentals of Cytotoxic Drug Reconstitution (CDR) and Parenteral Nutrition (PN) which was attended by fourth-year pharmacy students, DoCP lecturers, DoCP lab staff, a pharmacist, and two pharmacy assistants from Hospital Al-Sultan Abdullah (HASA) UiTM. The one-day workshop is an annual event aimed particularly at equipping the final year students with the basic knowledge and essential skills required for pharmacists working at PN and CDR units. In the hospital setting, CDR and PN provided by the pharmacy unit have long been recognised as specialised services in Malaysia. As the pharmaceutical care concept has evolved from product-entered to patient-centered, the roles of pharmacists in CDR and PN have also expanded to include pharmacists as integral members of the multi-disciplinary team providing CDR and PN services. Therefore, it is of paramount importance to expose our students to the expanding roles and responsibilities of CDR and PN pharmacists.